Dialogue Structures and Types - Galstyan, Ashot (Bulletin of Yerevan University B: Philology, 2024)
The main expression of human communication proceeds through verbal interaction, in which dialogues play a crucial role. Linguistic literature review suggests that dialogue structures are represented by the schemes A said – B said, or A asked – B answered. The interrogative patterns occupy a particular place in dialogues. Hence, interrogative intonation is the most characteristic feature of dialogues. There are diverse applications of dialogues. Literary discourse is generated through unique dialogue types such as internal, unilateral, unanswered, gesture-based-response, etc.Literary debates and ideological discrepancies can find their unique expression in fiction through poetic dialogues.
Keywords: verbal intercourse; intercultural dialogue; interrogative patterns; intonation; unique dialogues; literary debate; structure